Developing Indonesian Islamic ‎Civilization through Optimizing ‎Life-Based Islamic Education ‎Learning - Lilik Nur Kholidah‎ (Universitas Darussalam Gontor, 2021)
This article aims to examine the development of Islamic civilization through optimizing life-based Islamic religious education learning in order to improve the quality of Indonesian human resources in the era of knowledge. This life-based Islamic religious education learning approach is important, because it can be considered as an appropriate educational concept in the era of knowledge where learning is directed at increasing scientific ethos, motivation, creativity and developing the potential of learners. The use of library data along with the design of its implementation in higher education institutions, public universities in this article is to explore elaborately related to the optimization and contribution of Islamic religious education. Furthermore, as a basis for analyzing the concept of life-based Islamic religious education learning. The implication is that through life-based Islamic religious education learning, various life skills, efforts to master knowledge are developed systematically, continuously and sustainably throughout life, both when relaxing, having a family and in society. Harmonization of potential development between the realms of knowledge, attitudes, and skills through a life-based Islamic religious education learning approach can encourage students to have an awareness of lifelong religious learning and the ability to adapt to changes in science and technology, social, economic and cultural guidelines based on Islamic teachings. The concept of life-based Islamic religious education can be considered as a solution to overcome the problem of the low scientific ethos and national character as well as to improve the quality of life and the lives of students in the era of knowledge.